Palinspastic (pre-rift and -drift) fit of India and conjugate Antarctica and geological connections across the suture - Veevers, J. J. (Gondwana Research, 2009)
The passive continental margins of India and conjugate Antarctica (30 degrees-80 degrees E) have been reconstructed quantitatively by eliminating the intervening ocean floor. Recently acquired seismic and gravity data from the margins define the boundary between continental and oceanic crust (COB) and indicate the thickness of the extended (rifted) continental crust. The COBs are restored to their pre-rift position by eliminating pre-drift extension and are fitted together. This fully palinspastic reconstruction reveals the Lambert and Mahanadi Rifts aligned in a Permian-Triassic rift system, the Napier salient draped by the bight of India, and strong connections within each of four sectors: (1) Southern Granulite Terrain-Sri Lanka-Lutzow-Holm Terrane-Rayner Complex; (2) Napier-southern Eastern Ghats Mobile Belt-Dharwar Craton: (3) Kemp Land-MacRobertson Land-northern Eastern Ghats Mobile Belt-Bastar Craton: and (4) Prydz-Rauer-Vestfold Hills-Singhbhum Province. Major events registered are (a) a 0.9-1.3 Ga (Grenville) convergence that formed the Eastern Ghats-Rayner Mobile Belt in Rodinia, and (b) 0.50-0.60 Ga (Pan-Gondwanaland) events that accreted the Southern Granulite Terrain and Sri Lanka to the Antarctic-Indian region. Gondwanaland broke up at 0.14 Ga along the grain of the Eastern Ghats-Rayner Mobile Belt and across the composite Archean Dharwar-Napier Craton and the long axis of the Permian-Triassic rift system. (C) 2009 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.